The Safety of the Neighborhood Environment and Physical Activity in Czech and Polish Adolescents - Mitáš, Josef; Sas-Nowosielski, Krzysztof; Groffik, Dorota; Frömel, Karel (International journal of environmental research and public health, 2018)
(1) Background: An increase in or at least the sustainment of walking activities across a wide section of the population is a crucial health-related task for Central and East European countries. The aim of this study was to assess the associations between adolescents' walking activities and various levels of perceived safety of the built environment in differing socio-demographic backgrounds of Poland and the Czech Republic. Furthermore, we aimed to determine major moderators affecting the walking habits of adolescents in areas with different levels of walkability. (2) Methods: The surveys were conducted during the 2008-2009 and 2013-2014 school years in 24 Polish and 35 Czech secondary schools, with a sample of 2001 adolescents. All participants completed the International Physical Activity Questionnaire-Long Form and the NEWS-Abbreviated. Selected students took part in objective weekly monitoring of physical activity (PA). (3) Results: Boys and girls who perceived their neighborhood environment as the safest were significantly more likely to meet the recommendations for leisure-time walking. Adolescents from the safest environment achieved 11,024 steps/day on average, while those from the least safe environment achieved 9686 steps/day. (4) Conclusions: A safe neighborhood environment significantly predicts walking activities among girls. Environmental safety improvement can support the active transport and better use of leisure time PA.
Keywords: aktigrafie; průzkumy a dotazníky; Female; charakteristiky bydlení; Safety; Perception; ženské pohlaví; průřezové studie; Surveys and Questionnaires; Adolescent; volnočasové aktivity; percepce; lidé; cvičení; Environment Design; školy; Schools; Leisure Activities; built environment; Humans; Sex Factors; Actigraphy; Residence Characteristics; IPAQ-long form; Cross-Sectional Studies; Male; sexuální faktory; Czech Republic; Walking; životní prostředí - projekt; recommendation; bezpečnost; Česká republika; steps; mužské pohlaví; Poland; Exercise; mladiství; chůze; Polsko